Preparation of composite micro/nano structure on the silicon surface by reactive ion etching: Enhanced anti-reflective and hydrophobic properties. (May 2018) - Zeng, Yu; Fan, Xiaoli; Chen, Jiajia; He, Siyu; Yi, Zao; Ye, Xin; Yi, Yougen
Abstract: A silicon substrate with micro-pyramid structure (black silicon) is prepared by wet chemical etching and then subjected to reactive ion etching (RIE) in the mixed gas condition of SF6, CHF3 and He. We systematically study the impacts of flow rates of SF6, CHF3 and He, the etching pressure and the etching time on the surface morphology and reflectivity through various characterizations. Meanwhile, we explore and obtain the optimal combination of parameters for the preparation of composite structure that match the RIE process based on the basis of micro-pyramid silicon substrate. The composite sample prepared under the optimum parameters exhibits excellent anti-reflective performance, hydrophobic, self-cleaning and anti-corrosive properties. Based on the above characteristics, the composite micro/nano structure can be applied to solar cells, photodetectors, LEDs, outdoor devices and other important fields. Graphical abstract: Image 1 Highlights: The composite micro/nano structure be prepared by wet chemical etching and maskless reactive ion etching. The optimum parameters of the flow rates SF6, CHF3 and He, the etching pressure and the etching time are determined. The composite micro/nano structure endow the coating with properties of antireflection, hydrophobicity and self-cleaning.